NABi, a novel β-sheet breaker, inhibits Aβ aggregation and neuronal toxicity: Therapeutic implications for Alzheimer's disease - Jang, Ja-Young; Rhim, Hyangshuk; Kang, Seongman (Biochimica et biophysica acta. General subjects, 2018)
Amyloid beta (Aβ) aggregates are an important therapeutic target for Alzheimer's disease (AD), a fatal neurodegenerative disease. To date, AD still remains a big challenge due to no effective treatments. Based on the property that Aβ aggregates have the cross-β-structure, a common structural feature in amyloids, we systemically designed the Aβ-aggregation inhibitor that maintains Aβ-interacting ability but removes toxic part from SOD1 (superoxide dismutase 1)-G93A. We identified NABi (Natural Aβ Binder and Aβ-aggregation inhibitor) composed of β2–3 strands, a novel breaker of Aβ aggregation, which does not self-aggregate and has no cytotoxicity at all. The NABi blocks Aβ-fibril formation in vitro and in vivo and prevents neuronal cell death, a hallmark of AD pathogenesis. Such anti-amyloidogenic properties can provide novel strategies for treating AD. Furthermore, our study provides molecular insights into the design of amyloidogenic inhibitors to cure various neurodegenerative and amyloid-associated diseases, as NABi would regulate aggregation of other toxic β-sheet proteins other than Aβ. •Identification of NABi (Natural Aβ Binder and Aβ-aggregation inhibitor)•ΝABi specifically and strongly interacts with Aβ.•NABi is a novel inhibitor of Aβ-aggregation.•NABi prevents Aβ aggregate-induced neurodegeneration.•Implications for a potential AD therapeutic agent to block the neurodegeneration